Praktik Tambang Batu Kapur Dalam Perspektif Ekonomi Islam di Tuban Jawa Timur - Shahriyah, Siti; Fahrullah, A'rasy (Jurnal Ekonomika dan Bisnis Islam, 2021)
The purpose of this study was to determine a review from an Islamic economic point of view of the limestone mining practices in Tuban, East Java. This study uses a descriptive qualitative approach which aims to analyze the Islamic economic view of the limestone mining activity and its impacts in Tuban, East Java. The object taken is a mine site in Bektiharjo Village. This study uses primary data and secondary data to support the research process. Primary data obtained directly by the author from the results of interviews with sources. Meanwhile, secondary data were obtained from reading books and other literature. This study uses triangulation of sources and techniques as data validity, and uses Miles and Hubberman field data analysis models in the form of data reduction, data presentation, and data verification. The results of this study indicate that the existence of this limestone mining activity can create ample employment opportunities for local residents, however mining managers ignore the basic values of Islamic business ethics, namely balance, free will, and responsibility. In addition, economic pressure and the lack of public knowledge and awareness about the long-term impacts that may arise from mining activities are one of the factors that keep mining activities continuing.